Geriatricians’ knowledge of terminal care in patients with advanced dementia - Falvy-Bockos, Ian (2022)
Objective: To learn about the disagreements among geriatricians from a Latin American country (Peru) as to the palliative therapy for dementia. Materials and methods: A descriptive and cross-sectional study. The population consisted of Peruvian geriatricians and geriatrics residents surveyed during August 2019. A non-probability convenience sampling was used. Considering a total population of 277 geriatricians in Peru and a design effect of 1.0, the minimum sample size was 162 geriatricians. The survey included different questions focused on geriatricians’ decisions on the daily clinical practice of terminal care in dementia. To ensure a better understanding of the answers, a typical case of the disease was presented. Results: One hundred sixty-two (162) doctors were surveyed, most of whom were geriatricians (81.48 %). Regarding the global level of attitudes and knowledge of palliative care, 89.61 % considered dementia as a non-oncological terminal illness, and 69.18 % considered laboratory sample collection, peripheral intravenous line insertion, urinary catheterization and nasogastric tube insertion as invasive measures. Conclusions: The survey showed a moderate level in attitudes and knowledge of palliative care. The weakest points were the practical perspective and suitability in decision-making. Therefore, training programs aimed at making adequate prognoses and improving decision-making of physicians involved in the care and support of older adults with late-stage dementia should be conducted to avoid implementing measures that will not generate a positive impact to and will harm the patient's quality of life.